Shakespeare and the grammar of forgiveness - Beckwith, Sarah, 1959- (Cornell University Press, 2011)
"Shakespeare lived at a time when England was undergoing the revolution in ritual theory and practice we know as the English Reformation. With it came an unprecedented transformation in the language of religious life. Whereas priests had once acted as mediators between God and men through sacramental rites, Reformed theology declared the priesthood of all believers. What ensued was not the tidy replacement of one doctrine by another but a long and messy conversation about the conventions of religious life and practice. In this brilliant and strikingly original book, Sarah Beckwith traces the fortunes of this conversation in Shakespeare's theater.